Generation of α-Particle Beams With a Multi-kJ, Peta-Watt Class Laser System - Daniele Margarone; Daniele Margarone; Alessio Morace; Julien Bonvalet; Yuki Abe; Vasiliki Kantarelou; Didier Raffestin; Lorenzo Giuffrida; Philippe Nicolai; Marco Tosca; Antonino Picciotto; Giada Petringa; et al. (Frontiers in Physics, 2020)
We present preliminary results on generation of energetic α-particles driven by lasers. The experiment was performed at the Institute of Laser Engineering in Osaka using the short-pulse, high-intensity, high-energy, PW-class laser. The laser pulse was focused onto a thin plastic foil (pitcher) to generate a proton beam by the well-known TNSA mechanism which, in turn, was impinging onto a boron-nitride (BN) target (catcher) to generated alpha-particles as a result of proton-boron nuclear fusion events. Our results demonstrate generation of α-particles with energies in the range 8–10 MeV and with a flux around 5 × 109 sr−1.